Impact of tear film stability on corneal refractive power measurement and surgical planning for cataract - Yuanfeng Jiang; Xiteng Chen; Yichen Gao; Nan Gao; Huiyu Wang; Yanwen Feng; Meisa Li; Luning Qin; Fei Li; Shaozhen Zhao; Shaochong Bu; Fang Tian (Advances in Ophthalmology Practice and Research)
Purpose: This prospective cohort study aimed to assess the influence of tear film stability on corneal refractive power measurement and surgical planning in cataract patients. Methods: Participants were divided into tear film instability (tear film stability level 2) and control (level 0–1) groups based on Keratograph 5M results. Using IOL Master 700, two consecutive measurements were obtained with a 10-min interval. Parameters including standard keratometry (Kf, Ks and K), keratometric corneal astigmatism (KCA), total keratometry (TKf, TKs and TK) and total corneal astigmatism (TCA) were recorded. IOL power was calculated using SRK-T, SRK-T TK, Haigis, Haigis TK, Barrett Universal II, and Barrett Universal II TK formulas. Results: The results showed significantly higher differences between two measurements in Kf, K, KCA, TKf, TK, and TCA, as well as the vector variability of corneal astigmatism in the tear film instability group (all P ​< ​0.05). Of all formulas, only the SRK-T formula displayed significantly higher variability in IOL power calculations in the tear film instability group compared to the control group (P ​< ​0.05). Conclusions: This study highlights that tear film instability can lead to deviations in corneal refractive power and astigmatism measurements, contributing to increased prediction errors in IOL power calculation, particularly with the SRK-T formula.